Level and potential social-ecological factors associated with physical inactivity and sedentary behavior among Moroccan school-age adolescents: a cross-sectional study - Abdelghaffar El-ammari; Hicham El kazdouh; Siham Bouftini; Samira El fakir; Youness El achhab (Komiyama Printing Co. Ltd, 2017)
Abstract Background Creating a successful intervention that supports an active lifestyle and prevents sedentary one requires a better understanding of the factors associated with physical inactivity (PI) and sedentary behavior (SB). However, these factors have not been assessed among Moroccan adolescents. This study aimed to determine prevalence of PI and SB and to explore their potential social-ecological associated factors in school-age adolescents. Methods In this cross-sectional study, 764 students (age range, 14-19 years) were enrolled from six schools in Taza city, Morocco. The Global School-based Student Health Survey was used to collect data about variables. We used bivariate and multivariate analyses to assess relations between dependent and independent variables. Results Overall, the prevalence of PI was 79.5% and SB was 36.5%. Among girls, these rates were higher (87.0 and 39.1%, respectively) than rates shown in boys (70.9 and 33.6%, respectively). In the multivariate logistic regression analysis, PI was associated with the following variables: illiterate father, hunger, suicidal ideation, inadequate vegetable consumption, and absence from physical education classes. Age, inadequate vegetable consumption, and absenteeism were associated with SB. Conclusions The prevalence of PI and SB is high, especially among girls. Thus, there is an urgent need to implement appropriate interventions to reduce PI and SB levels in secondary school-age adolescents and the associated factors identified can be useful.